Personality Traits And Emotional Arousal And Their Relationship To The Orientation Towards Athletic Excellence Dimensions Among Basketball Athletes - Harizi Abdenour ., (sports creativity, 2025)
: Abstract This study aims to investigate the correlations between Eysenck’s personality traits (extraversion and emotional stability), emotional arousal and athletic excellence dimensions among Basketball Players at the National Sports High-School of DRARIA. These correlations were served as variables for GABNA. The study was conducted on a sample of student-athletes (15 female and 22 male high-school basketball players for the a. y. 2017/2018). A Descriptive Correlational approach was used. EPQS, CEAS, and AEDs psychometrics were examined by the use of SPSS software. The results indicate that there are no correlations between extraversion, emotional instability and athletic excellence dimensions on the one hand and emotional arousal and athletic excellence dimensions on the other hand. Most of the findings show that there are no statistically significant differences between the variables representing athletic excellence dimensions, among both female and male basketball players. Besides, there are only statistically significant differences between the variable representing respect for others in favour of males. Thus, the absence of a correlation between the variables mentioned is attributed to a shortage in the number of samples tested. .